Relevance of the Value of Legal Certainty in the Appointment of Islamic Law Graduates as Notaries - Lingga, Firdo; Syah, Danial; Harahap, Herlina Hanum (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2021)
Sumiritas in the explanation of Article of Act No. 2 of 2014 on the Notary Department has resulted in uncertainty about the position of the Master of Islamic Law/Syariah as a Notary. This paper aims to analyze and dissect the issue of the appointment of graduates of Islamic law scholars as notaries. The research method in this writing is normative juridical. Sumiritas Article 3 of Act No. 2 of 2014 on the Notary Position has resulted in uncertainty for the status of a Master of Syariah Law as a Notary. This clearly results in uselessness for the Bachelor of Syariah Law in terms of the application of expertise and knowledge of Syariah law.